Oxidative NHC catalysis for the generation of imidoyl azoliums: synthesis of benzoxazoles - Patra, Atanu; James, Anjima; Das, Tamal Kanti; Biju, Akkattu T. (Journal of Organic Chemistry, 2018)
N-Fleterocyclic carbene (NHC)-catalyzed intramolecular cyclization of aldimines generated from 2-amino phenols and aromatic aldehydes leading to the synthesis of 2-arylbenzoxazoles under mild conditions is presented. The reaction proceeds via the generation of the aza-Breslow intermediates from imines and NHC, which under oxidative conditions form the key imidoyl azoliums and a subsequent intramolecular cyclization furnishes the product. The reaction tolerates a broad range of functional groups, and the products are formed in generally good yields.